2019
DOI: 10.1140/epjst/e2018-800076-1
|View full text |Cite
|
Sign up to set email alerts
|

Photon pair production by STIRAP in ultrastrongly coupled matter-radiation systems

Abstract: Artificial atoms (AA) offer the possibility to design physical systems implementing new regimes of ultrastrong coupling (USC) between radiation and matter [1], where previously unexplored non perturbative physics emerges. While experiments so far provided only spectroscopic evidence of USC, we propose the dynamical detection of virtual photon pairs in the dressed eigenstates, which is a "smoking gun" of the very existence of USC in nature. We show how to coherently amplify this channel to reach 100% efficiency… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…It has been shown that USC can give rise to several new interesting physical effects [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Ultrastrong coupling has been achieved in a variety of cavity-QED and other hybrid condensed-matter systems, including semiconductor polaritons in quantum wells [35][36][37][38][39], superconducting quantum circuits [40][41][42][43][44][45][46][47][48][49][50][51][52][53], a terahertz metamaterial coupled to the cyclotron resonance of a two-dimensional electron gas (2DEG) [54][55][56][57][58], organic molecules [59][60][61][62][63][64], and in an optomechanical system where a plasmonic picocavity was coupled ...…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that USC can give rise to several new interesting physical effects [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Ultrastrong coupling has been achieved in a variety of cavity-QED and other hybrid condensed-matter systems, including semiconductor polaritons in quantum wells [35][36][37][38][39], superconducting quantum circuits [40][41][42][43][44][45][46][47][48][49][50][51][52][53], a terahertz metamaterial coupled to the cyclotron resonance of a two-dimensional electron gas (2DEG) [54][55][56][57][58], organic molecules [59][60][61][62][63][64], and in an optomechanical system where a plasmonic picocavity was coupled ...…”
Section: Introductionmentioning
confidence: 99%
“…We checked the dynamics for AAs, and we reproduced results of Fig. 3 using half of the value of g 49 . We also checked that the protocol is robust against possible inhomogeneities of the individual couplings of AAs and the possible presence of stray additional modes at multiple frequencies.…”
Section: Resultsmentioning
confidence: 99%
“…STIRAP in superconducting nanocrcuits has been studied theoretically [27][28][29] and experimentally [30,31] since it can be used for new type of quantum gates [32] possibly resilient to solid state quantum noise [33][34][35][36][37][38]. In the USC scenario STIRAP can be used to detect virtual photons in the dressed eigenstates of the system, by coherently amplifying their conversion to real photons [16,24,25]. We consider a three-level atom (basis {|u , |g , |e }) ultrastrongly coupled to a single light mode of frequency ω c , resonant with the e.gtransition energy ε, described by the Hamiltonian…”
Section: Generation Of Two-photon Pairs By Stirapmentioning
confidence: 99%
“…where W s/p is the Stokes/pump field amplitude, τ is the delay, T is width of the pulses [16,25]. It may yield ∼ 100% coherent population transfer |0u → |2u iff Φ 0 |H c |nu = 0, i.e., the Rabi ground state contains pairs of virtual photons.…”
Section: Generation Of Two-photon Pairs By Stirapmentioning
confidence: 99%